Diabetes Self-Management Education (DSME) – Effect on Knowledge, Self-Care Behavior, and Self-Efficacy Among Type 2 Diabetes Patients in Ethiopia: A Controlled Clinical Trial - Hailu FB (Dove Medical Press, 2019)
Fikadu Balcha Hailu,1,2 Anne Moen,1 Per Hjortdahl1 1Institute for Health and Society, Faculty of Medicine, University of Oslo, Oslo, Norway; 2School of Nursing and Midwifery, Jimma University, Jimma, EthiopiaCorrespondence: Fikadu Balcha HailuInstitute for Health and Society, Faculty of Medicine, University of Oslo, Oslo, NorwayTel +251 911 00 4133Fax +251 471 111450Email fikadubalcha@gmail.comPurpose: Diabetes patients must be equipped with the necessary knowledge to confidently undertake appropriate self-care activities. We prepared a diabetes self-management education (DSME) intervention and assessed how it affected patients’ self-reported levels of diabetes knowledge, self-care behaviors, and self-efficacy.Patients and methods: A before-and-after, two-group intervention study was conducted at Jimma University Medical Centre among adult patients with type 2 diabetes. At baseline, we randomly assigned 116 participants to the DSME intervention and 104 to a comparison group. Six interactive DSME sessions supported by an illustrative handbook and fliers, experience-sharing, and take-home activities were administered to the intervention group by two nurses during a six-month period. Diabetes knowledge, self-care behaviors, and self-efficacy were measured at baseline and at nine months following the commencement of DSME intervention (endpoint) in both groups.Results: At the endpoint, data from 78 intervention group participants and 64 comparison group participants were included in final analysis. The difference in the mean Diabetes Knowledge Scale scores before and after the DSME intervention was significantly greater in the intervention group (p = 0.044). The measured self-care behaviors included diet, exercise, glucose self-monitoring, footcare, smoking, alcohol consumption, and khat chewing. The mean number of days per week on which the intervention group participants followed general dietary recommendations increased significantly at the endpoint (p = 0.027). The intervention group followed specific dietary recommendations (p = 0.019) and performed footcare (p = 0.009) for a significantly greater number of days. There were no significant differences within or between the groups in other self-reported diabetes self-care behavior regimens or in diabetes self-efficacy.Conclusion: Our study found significant improvements in the intervention participants’ diabetes knowledge scores and in their adherence to dietary and footcare recommendations. This demonstrates that our DSME intervention may be of clinical importance in developing countries such as Ethiopia.Trial registration: ClinicalTrials.gov, Identifier NCT03185689, retrospectively registered on June 14, 2017: https://clinicaltrials.gov/ct2/show/NCT03185689.Keywords: nurse-led DSME, diabetes knowledge, self-care behavior, self-efficacy